2019
DOI: 10.1101/579607
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of a novel gammaherpesvirus in Canada lynx (Lynx canadensis)

Abstract: Gammaherpesviruses (GHVs) infect many animal species and are associated with lymphoproliferative disorders in some. Previously, we identified several novel GHVs in North American felids, however a GHV had never been identified in Canada lynx (Lynx canadensis). We therefore hypothesized the existence of an unidentified GHV in lynx. Using degenerate nested and subsequently virus-specific PCR, we amplified and sequenced 3.4 kb of DNA from a novel GHV in lynx, which we named Lynx canadensis gammaherpesvirus 1 (Lca… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…New data on gammaherpesviruses come from Hendrikse et al, who identified a novel gammaherpesvirus in Canada lynx ( Lynx canadensis ), LcaGHV1, in 36% of samples from USA and 17% from Canada [ 27 ]. Novacco et al report a molecular prevalence of FcaGHV1, the domestic cat gammaherpesvirus, of 5.5% to 6.0% among domestic cats in Switzerland.…”
Section: Introductionmentioning
confidence: 99%
“…New data on gammaherpesviruses come from Hendrikse et al, who identified a novel gammaherpesvirus in Canada lynx ( Lynx canadensis ), LcaGHV1, in 36% of samples from USA and 17% from Canada [ 27 ]. Novacco et al report a molecular prevalence of FcaGHV1, the domestic cat gammaherpesvirus, of 5.5% to 6.0% among domestic cats in Switzerland.…”
Section: Introductionmentioning
confidence: 99%